Generating Functions for Some Hypergeometric Functions of Four Variables via Laplace Integral Representations - Jihad Younis; Maged Bin-Saad; Ashish Verma (Journal of Function Spaces)
Generating functions plays an essential role in the investigation of several useful properties of the sequences which they generate. In this paper, we establish certain generating relations, involving some quadruple hypergeometric functions introduced by Bin-Saad and Younis. Some interesting special cases of our main results are also considered.